Lack of B-RAF mutations in head and neck squamous cell carcinoma - Al Sheikh Ali, M; Gunduz, M; Gunduz, E; Tamamura, R; Beder, L; Tominaga, S; Onoda, T; Yamanaka, N; Grenman, R; Shimizu, K; Nagai, N; Nagatsuka, H (Folia biologica (Praha), 2008)
B-RAF is one of the most commonly mutated oncogenes in human cancer. However, the mutation status of B-RAF has not been established completely in HNSCC. We have analysed the mutation status of the kinase domain of the B-RAF gene (exons 11 and 15) in 91 Japanese HNSCC patients as well as 12 HNSCC cell lines. DNA was extracted and amplified by PCR. Mutations were then analysed by SSCP mutation detection method. Since V600EB-RAF constitutes 90 % of the mutations identified in B-RAF in human cancers, we also used MASA analysis to specifically detect this mutation in exon 15 of B-RAF. Using both methods, no mutation was found in both exon 11 and 15 in all patients and cell lines. Mu tations are absent or rare in the kinase domain of B-RAF in Japanese HNSCC. However, more studies are still needed to determine its usefulness as a target for molecular therapy in these patients.
Keywords: alely; Polymorphism, Single-Stranded Conformational; exony; Humans; Proto-Oncogene Proteins B-raf; mutační analýza DNA; mutace; polymorfismus konformace jednovláknové DNA; Alleles; Exons; lidé; nádory hlavy a krku; Head and Neck Neoplasms; protoonkogenní proteiny B-raf; DNA Mutational Analysis; polymerázová řetězová reakce; Polymerase Chain Reaction; nádorové buněčné linie; spinocelulární karcinom; Carcinoma, Squamous Cell; Cell Line, Tumor; Mutation